IOT - development of a home automation system 1 - Tan, Kim Seng (Nanyang Technological University, 2024)
The demand for seamless integration of Internet of Things (IoT) devices with industry giants like Google Assistant and Amazon Alexa are increasing with smart home ecosystems. This paper emphasises the potential of utilising Espressif Systems (ESP) 32 and 8266 microcontrollers to create an IoT home solution that can seamlessly integrate with these smart home assistants. It specifically explores the use of ESP Rainmaker, a platform simplifying the connection between self-created ESP-IoT devices and smart home ecosystems. By integrating with smart home assistants, it introduces a wider range of compatible devices and enables the creation of new scenarios, such as automation, allowing users to customise according to preferences and needs. Additionally, the paper highlights the advantages of using the energy-efficient ESP-Now protocol in IoT applications, contributing to power conservation and sustainability of IoT networks. Three practical examples demonstrate the implementation of ESP Rainmaker and ESP-Now in IoT home solutions, showcasing the platform's versatility in enabling unique smart functionalities tailored to specific requirements. Through practical demonstrations and analysis, this paper contributes to the advancement of IoT within smart homes, highlighting ESP as a versatile platform that empowers users to develop innovative solutions for modern home living